Characterization and Determination of the Antibacterial Activity of Baccharis dracunculifolia Essential-Oil Nanoemulsions - Erika da Silva Monteiro; Franklyn Santos da Silva; Karolina Oliveira Gomes; Bruno Alcântara do Prado; Rebeca Dias dos Santos; Claudio Augusto Gomes da Camara; Marcilio Martins de Moraes; Izabel Cristina Rodrigues da Silva; Vinicius Teixeira de Macêdo; Guilherme Martins Gelfuso; Lívia Cristina Lira de Sá Barreto; Daniela Castilho Orsi (MDPI AG, 2023)
The aim of this study was to evaluate the antibacterial activity of nanoemulsions of Baccharis dracunculifolia essential oil. The volatile compounds of the essential oil were identified using gas chromatography-mass spectrometry. The properties of the nanoemulsions (droplet size, polydispersity index, pH, and electrical conductivity) were determined. The antibacterial activities of the essential oil and its nanoemulsions were evaluated using MIC, MBC, and disk diffusion. The microorganisms used were: Gram-positive bacteria (Staphylococcus aureus ATCC 25923, Bacillus cereus ATCC 14579, Streptococcus mutans ATCC 25175, and Enterococcus faecalis ATCC 29212) and Gram-negative bacteria (Pseudomonas aeruginosa ATCC 27853, Klebsiella pneumoniae ATCC BAA-1706, Salmonella enterica ATCC 14028, and Escherichia coli ATCC 25922). The major volatile compounds of the B. dracunculifolia essential oil were limonene (19.36%), (E)-nerolidol (12.75%), bicyclogermacrene (10.76%), and β-pinene (9.60%). The nanoemulsions had a mean droplet size between 13.14 and 56.84 nm. The nanoemulsions presented lower and statistically significant MIC values compared to the essential oil, indicating enhancement of the bacteriostatic action. The disk diffusion method showed that both the nanoemulsions and the essential oil presented inhibition zones only for Gram-positive bacteria, while there were no results against Gram-negative bacteria, indicating that B. dracunculifolia essential oil has a better antimicrobial effect on Gram-positive microorganisms.